Research-informed development of comprehensible isiXhosa teaching material: the Department of Basic Education Mental Starters doubling and halving unit - Booi, Tabisa (Rhodes University, Faculty of Education, Department of Primary and Early Childhood Education)
One of the challenges faced by schools that teach in isiXhosa in the Foundation Phase is the impact of nature of language used in the early-grade mathematics classroom. This is the focus of this research study. Despite numerous programs addressing the poor performance in mathematics, a significant majority of interventions are presented in English, creating barriers for learners and teachers using their native languages. While the Language in Education Policy allows for home language instruction in isiXhosa, the translation of materials often contains distortion in meaning and unfamiliar terms, complicating comprehension for indigenous language learners. Motivated by concerns over low mathematics performance, as highlighted in TIMSS (2019), and my personal experiences in teaching Foundation Phase mathematics in isiXhosa at a rural primary school, this study explores the challenges arising from using translated materials. The use of mediating materials in isiXhosa can be hindered by unfamiliar terms and distortion in meaning. For this reason, I adopted a translanguaging approach, incorporating transliteration between English and isiXhosa, especially in mathematics teaching. Grounded in the pragmatism paradigm, this qualitative design research unfolds in an isiXhosa medium primary school in Makhanda. The investigation centers first on document analysis of the Doubling and Halving unit in the Mental Starters Assessment Programme (MSAP) Teacher Guide (in English and isiXhosa), and then focuses on the teaching of two grade 3 classes, in isiXhosa, using the MSAP Doubling and Halving teaching sequence. Two grade 3 teachers and their principal participate as critical friends. The key research questions are: (1) What are the enablers and constraints that are experienced by the teacher during the mediation of the doubling and halving calculating strategies in isiXhosa?; (2) What are the key terms and phrases (vocabulary) needed to teach doubling and halving in isiXhosa?; (3) What are the perspectives and pedagogical insights of the critical friends on the isiXhosa vocabulary that was developed? The research unfolds in multiple stages, beginning with a document analysis of the MSAP using Toury's Descriptive Translation Studies. Subsequently, I adapt eight lesson starters for doubling and halving, implementing them across two grade 3 classes in a double action research cycle. Focus group discussions with critical friends, aided by video recordings for stimulated recall, provide valuable insights. Data collected throughout these stages are analyzed through the lens of Vygotsky's Socio-Cultural theory, contributing to a comprehensive understanding of the challenges and potential solutions in this educational context.
Keywords: Native language and education -- South Africa; Mathematics Translating -- South Africa; South Africa. Department of Basic Education; Translanguaging (Linguistics); Mathematics-- Study and teaching (Elementary) -- South Africa